Preparation of ultrafine spherical nickel powders - SI Jia-jia; SU Xiao-lei (Fenmo yejin jishu)
Ultrafine nickel powders were synthesized by liquid phase reduction using water as the reaction system and hydrazine hydrate as the reducing agent without the dispersant and surfactant. The powders were characterized by scanning electron microscope (SEM), X-ray diffractometer (XRD), laser particle size analyzer, and energy disperse spectroscope (EDS). The effects of the reaction temperature and [N2H4]/[Ni2+] concentration ratio on the average particle size, morphology, dispersibility, reduction rate, and purity of the nickel powders were investigated. The variation of the powder dispersibility during the morphology transformation of nickel powders from thorn spherical to spherical was discussed. The results show that, under the reaction temperature of 80 ℃ and [N2H4]/[Ni2+]=8, the prepared nickel powders show the high purity, good sphericity, narrow particle size distribution, and high reduction rate with the average particle size of 380 nm.